Improving the Quality of Life of Patients with Headache Treated with Neural Therapy - Nassar Tobón, Andrea Catalina; Geney Montes, María Cristina; Martínez Pacheco, Fabio Heliodoro; Muñoz-Sellart , Montserrat; Vinyes, David (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
Primary headaches (PHs) are common health complaints with a high impact on health-related quality of life (HRQOL). Treatment is multifactorial, including pharmacological and non-pharmacological strategies. Neural therapy (NT) is a regulatory treatment system that uses local anesthetic injections in chosen points to treat pain. This study aims to evaluate the effect of NT on the HRQOL of patients with PHs. Quasi-experimental prospective study involving 93 patients treated. The impact on HRQOL was evaluated through the SF-36 health, before and after treatment. Seven out of the eight items measured on the SF-36 scale improved after the intervention (p<0.001).